The Nano-Casein-Phenolic Properties Using Different Reassembling Temperature (Faculty of Animal Science Universitas Brawijaya, 2023)
Casein is one of the milk proteins which have the unique characteristic, it is called assembly. Assembly is casein can interact with casein or others to form micelle casein nanoparticle. The nano size of casein can accelerate the process of absorption into the body, making it suitable as a delivery system of nutraceutical food. It can happen with the appropriate temperature. According to the statement, this research aims to determine the best temperature for the reassembling process of casein with phenolic at different temperature (40°C, 50°C, and 60°C) with four replications.